The Management of Glucocorticoid Therapy in Liver Failure - Xue, Ran; Meng, Qinghua (Frontiers in Immunology, 2019)
Liver failure is characterized by rapid progression and high mortality. Excessive systemic inflammation is considered as the trigger of liver failure. Glucocorticoids (GCs) can rapidly suppress excessive inflammatory reactions and immune response. Actually, since the 1970s, GCs have been applied in the treatment of liver failure. However, until now, the using of GCs in the treatment of liver failure has been still unclear and controversial. Some brand new researches regarding the molecular mechanisms of GCs may explain the GCs controversial actions in liver failure. More results should be confirmed in a larger randomized clinical trial helping to arrive to better definitions in terms of treatment schedules according to different clinical settings. Meanwhile, the timing and dosing of GCs in the treatment of liver failure should also be explored.